1988
DOI: 10.1002/chin.198841017
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Electrophysical Properties of the Compounds Cu2A(II)B(IV)Se4 (A(II): Cd, Hg; B(IV): Ge, Sn).

Abstract: ChemInform Abstract The title compounds are prepared from the elements in evacuated quartz ampoules, which are heated to 1150-1350 K. The temp. dependences of the specific electric conductivities, of the Hall coefficients and of the thermoelectromotive forces are determined between 150 and 950 K. Furthermore the width of the forbidden zone, the microhardness, the pyknometric density and the lattice parameters are determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Mkrtchyan et al [1] showed that the Cu 2 CdGeSe 4 crystals at room temperature have p-type conductivity, and the thermal bandgap energy is 1.20 eV.…”
Section: The Cu 2 Gese 3 -Cdse Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Mkrtchyan et al [1] showed that the Cu 2 CdGeSe 4 crystals at room temperature have p-type conductivity, and the thermal bandgap energy is 1.20 eV.…”
Section: The Cu 2 Gese 3 -Cdse Systemmentioning
confidence: 99%
“…for Cu 2 CdGeSe 4 [1]) make them promising materials for the heterojunctions for the conversion of solar and polarized radiation based on the wide-band, n-type B II X semiconductors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cu 2 CdGeSe 4 is a typical p-type semiconductor with optical energy gap value equal to 1.29 eV [ 10 ] or 1.20 eV [ 11 ] and strong optical anisotropy. Its microhardness is equal to 1.90 GPa [ 9 ] or 2.32 GPa [ 12 ], and its density is equal to 5.45 g/cm 3 [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The three compounds are characterized by high absorption coefficients and direct band gaps that narrow with the atomic weight of the II element; from 1.0-1.4 eV for CZTSe to 0.89-0.96 eV for CCTSe and 0.17 eV for CHTSe. 4,[7][8][9] Crystallographically, the three compounds display diamondlike phases. [10][11][12] However, the distribution of the cations within the unit cell depends on the nature of the II element.…”
Section: Introductionmentioning
confidence: 99%